Analysis of the June Bag Project Into Quality Goods - Yuli Indah Fajar Dini; Dedy Cahyono; Diva Maharani; Micheal Hui; Selina Selina (Universitas Muhammadiyah Makassar, 2024)
Abstract:TasGon, short for Jute Bag, is an innovation that transforms jute waste into useful, environmentally friendly and high quality items. In this project, jute waste is collected, processed into jute fiber, and made into bags which have multiple benefits for the environment and society. The project management process includes project integration, scope management, time management, cost management, quality management, human resource management, communications management, risk management, and procurement management. Various project management tools and techniques are used, such as network planning, critical paths, Pareto diagrams, and Ishikawa diagrams, to ensure the project goes according to plan and meets established quality standards. The project conclusion emphasizes the importance of thorough planning, proactive risk management, effective communication, and collaboration between stakeholders. Suggestions for improving your understanding and project management skills include practicing on real projects, improving communication skills, continuing to learn and adapt, utilizing tools and technology, and collaborating with fellow students and experts. By implementing these suggestions, project managers can become more effective in managing future projects.